2007
DOI: 10.1007/s10350-006-0882-x
|View full text |Cite
|
Sign up to set email alerts
|

A Nonsurgical Means of Fecal Diversion: The Zassi Bowel Management System

Abstract: The Zassi Bowel Management System tube allows diversion of feces away from the perineum for wound healing. It is safe, effective, and may help avoid stoma formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 5 publications
(5 reference statements)
0
62
1
1
Order By: Relevance
“…Proprietary faecal diversion systems are available in the market which can be inserted into the rectum and faeces collected in a bag while the perineal wound is protected. These systems may help in avoiding a stoma in patients requiring faecal diversion [15].…”
Section: Discussionmentioning
confidence: 99%
“…Proprietary faecal diversion systems are available in the market which can be inserted into the rectum and faeces collected in a bag while the perineal wound is protected. These systems may help in avoiding a stoma in patients requiring faecal diversion [15].…”
Section: Discussionmentioning
confidence: 99%
“…Keshava et al [9] reported 20 patients (13 severe perineal excoriations and only 7 perineal burns). They used the Zassi Bowel Management System (Zassi BMS) for fecal containment.…”
Section: Discussionmentioning
confidence: 99%
“…We had to perform colostomy in one patient with delayed wound healing (>29 days). Keshava et al [9] reported that they had used the Zassi BMS in one patient for 59 days without any mucosal injury. They exceeded 29 days only in this patient; the mean duration of catheterization was 21 days in their study, which was similar to our study (22.5 days).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluate skin for fungal infection associated with fecal incontinence 38,51 Assess skin, development of incontinence-associated dermatitis, as well as frequency and consistency of stool to determine need for a fecal containment device 42,44,[57][58][59][60][61][62] Assess resolution of cause of diarrhea, changes in diarrhea flow, consistency, and skin condition to determine need for ongoing fecal containment device [57][58][59][60][61][62] Evidence-based intervention…”
Section: Related Beliefs and Current Evidencementioning
confidence: 99%
“…The researchers found that the device did not harm the rectal mucosa (by performing endoscopy at baseline and after removal of the BMS), perigenital skin condition improved in 92% of the patients, and the health care providers reported that the system was easy to manage. Keshava et al 61 conducted a prospective study of inpatients admitted for burn management or to the geriatric unit. Twenty-two patients with diarrhea were managed with a BMS.…”
Section: Related Beliefs and Current Evidencementioning
confidence: 99%